Distribution and abundance of Tule Geese in California and southern Oregon - Wege, Michael L (Wildfowl, 1984)
Migration stopover areas, wintering areas, and winter population estimates were recorded for Tule Geese Anser albifrons gambelli from 1978 to 1982. Autumn migration stopover areas were Summer Lake WMA, Oregon (1500-2100 birds) and Klamath Basin NWRs, California (1200-2000 birds). The primary wintering areas were the northern Sacramento Valley (Sacramento and Delevan NWRs, 3500 birds) and the Suisun Marsh (Grizzly Island WA, 1200-1500 birds). Klamath Basin NWRs (1000-3000 birds) were the only major spring migration stopover areas located. The 1980-81 and 1981-82 winter populations of Tule Geese in California were estimated to be about 5000 birds.